A USA Africa collaborative strategy for identifying, characterising and developing maize germplasm with resistance to aflatoxin contamination - Menkir, A.; Brown, R.L.; Bandyopadhyay, Ranajit; Chen, Z.Y.; Cleveland, T.E. (2006)
Aflatoxin contamination of maize by Aspergillus flavus poses serious potential economic losses in the US and health hazards to humans, particularly in West Africa. The Southern Regional Research Center of the United States Department of Agriculture, Agricultural Research Service (USDA-ARS-SRRC) and the International Institute of Tropical Agriculture (IITA) initiated a collaborative breeding project to develop maize germplasm with resistance to aflatoxin accumulation. Resistant genotypes from the US and selected inbred lines from IITA were used to generate backcrosses with 75% US germplasm and F1 crosses with 50% IITA and 50% US germplasm. A total of 65 S4 lines were developed from the backcross populations and 144 S4 lines were derived from the F1 crosses. These lines were separated into groups and screened in SRRC laboratory using a kernel-screening assay. Significant differences in aflatoxin production were detected among the lines within each group. Several promising S4 lines with aflatoxin values significantly lower than their respective US resistant recurrent parent or their elite tropical inbred parent were selected for resistance-confirmation tests. We found pairs of S4 lines with 75–94% common genetic backgrounds differing significantly in aflatoxin accumulation. These pairs of lines are currently being used for proteome analysis to identify resistance-associated proteins and the corresponding genes underlying resistance to aflatoxin accumulation. Following confirmation tests in the laboratory, lines with consistently low aflatoxin levels will be inoculated with A. flavus in the field in Nigeria to identify lines resistant to strains specific to both US and West Africa. Maize inbred lines with desirable agronomic traits and low levels of aflatoxin in the field would be released as sources of genes for resistance to aflatoxin production.